Perancangan Sistem Pencatatan Akuntansi Pada Pt. Aroma Nusajaya Karya - Robby Krisyadi; Andi Andi (Universitas Internasional Batam, 2021)
The purpose of this PkM is to design adjusted accounting system report for a company or firm in accordance with accounting standard. The object of this PkM is PT. Aroma Nusajaya Karya which located at Ruko Cahaya Garden Block D1 No.2, Batam City. Data collection method is do some observation, interview, designing, and simulation. The accounting system report is designed by using Microsoft Access software application that has been adjusted to the needs and conditions of the company with the accounting standard (SAK) for EMKM. Generated financial reports by the system is, profit and loss report, financial position report, ledger, trial balance report, sales and purchases report, also receivables and payables report. The result of the PkM showed that by implementing the accounting system report at PT. Aroma Nusajaya Karya, it can assist the owner of the company in monitoring their business performance and decision making to achieve greater profits. It is recommended for the next PkM to learn book keeping and accounting in order to be able to grasp the concept before implementing and designing the system.